Emergency Physician Perspectives on Central Venous Catheterization in the Emergency Department: A Survey‐based Study. (June 2014) - Ballard, Dustin W.; Reed, Mary E.; Rauchwerger, Adina S.; Chettipally, Uli K.; Offerman, Steven R.; Mark, Dustin G.; Vinson, David R.; the Kaiser Permanente CREST Network Investigators; Merchant, Roland C.
Abstract Objectives The objective was to assess clinician experience, training, and attitudes toward central venous catheterization (CVC) in adult emergency department (ED) patients in a health system promoting increased utilization of CVC for severely septic ED patients. Methods The authors surveyed all emergency physicians (EPs) within a 21‐hospital integrated health care delivery system that had recently instituted a modified Rivers protocol for providing early goal‐directed therapy (EGDT) to patients with severe sepsis or septic shock, including CVC if indicated. This initiative was accompanied by a structured, but optional, systemwide hands‐on training for EPs in real‐time ultrasound‐guided CVC (US CVC). EPs' responses to questions regarding self‐reported experience with CVC in the ED are reported. Data included frequency of CVC (by type) and US CVC training opportunities: both during and after residency and informal ("on‐the‐job training involving actual ED patients under the oversight of someone more experienced than yourself") and formal ("off‐the‐job training not involving actual ED patients"). The survey also asked respondents to report their comfort levels with different types of CVC as well as their agreement with possible barriers (philosophical, time‐related, equipment‐related, and complication‐related) to CVC in the ED. Multivariable ordinal logistic regression was used to identify provider characteristics and responses associated with higher yearly CVC volumes. Results The survey response rate among eligible participants was 365 of 465 (78%). Overall, 154 of 365 (42%) respondents reported performing 11 or more CVCs a year, while 46 of 365 (13%) reported doing two or fewer. Concerning CVC techniques, 271 of 358 (76%) of respondents reported being comfortable with the internal jugular approach with US guidance, compared to 200 of 345 (58%) with the subclavian approach without US. Training rates were reported as 1) in residency, formal 167 of 358 (47%) and informal 189 of 364 (52%); and 2) postresidency, formal 236 of 359 (66%) and informal 260 of 365 (71%). The most commonly self‐reported barriers to CVC were procedural time (56%) and complication risk (61%). After multivariate adjustment, the following were significantly associated with greater self‐reported CVC use (p < 0.01): 1) informal bedside CVC training after residency, 2) male sex, 3) disagreement with complication‐related barrier questions, and 4) self‐reported comfort with placing US‐guided internal jugular catheters. Conclusions In this cross‐sectional survey‐based study, EPs reported varying experience with CVC in the ED and reported high comfort with the US CVC technique. Postresidency informal training experience, male sex, negative responses to complication‐related barrier questions, and comfort with placing US‐guided internal jugular catheters were associated with yearly CVC volume. These results suggest that higher rates of CVC in eligible patients might be achieved by informal training programs in US and/or by disseminating existing evidence about the low risk of complications associated with the procedure.